Transgenic Canola Oil Improved Blood Omega-3 Profiles: A Randomized, Placebo-Controlled Trial in Healthy Adults - Lin, Xinjie Lois; Baisley, Joshua; Bier, Anthony; Vora, Drasty; Holub, Bruce (Frontiers in Nutrition, 2022)
Long-chain omega-3 polyunsaturated fatty acids (LC-ω3 PUFA), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), play key roles in physiological functions and disease prevention. The nutrient gap in meeting LC-ω3 intake recommendations in the U.S. and globally can be addressed by alternative sources of LC-ω3. This randomized, placebo-controlled, seamless phase I/II study evaluated the pharmacokinetics, safety, and efficacy of a transgenic LC-ω3-rich canola oil in healthy adults. Participants (n=33/group) were randomized to receive low-, mid-, or high-dose of the LC-ω3-rich oil (providing 285, 570, or 1140 mg LC-ω3 PUFA respectively) or placebo (corn oil). After one dose, plasma ω3 (primary outcome) levels were assessed over a 72-hour pharmacokinetic period. Whole blood and red blood cells (RBC) ω3 and serum cardiovascular biomarkers were assessed during a 16-week continuation period with daily supplementation. Compared to low-dose and placebo, high-dose group showed greater DHA AUC0-72h and Cmax. A linear response was observed for DHA and EPA AUC0-72h. Compared to placebo, high- and mid-dose groups showed increased whole blood DHA, EPA, α-linolenic acids (ALA) (high-dose only), omega-3 score, and omega-3 index after 4 weeks, and increased DHA and EPA in RBC after 16 weeks (P<0.05). No changes in cardiovascular biomarkers were seen. Overall, this LC-ω3-rich oil demonstrated good DHA bioavailability and significantly improved short and long-term blood LC-ω3 profiles. Sixteen weeks of daily supplementation of the LC-ω3-rich oil was safe and well tolerated.